Emergency Caesarean Section and Idiopathic Intracranial Hypertension: Case Report - Khaoua, Lamiaa; Benakrout, Aziz; Lahbabi, Sophia; Oudghiri, Pr Nezha; Saoud, Pr Anas Tazi (Archives of Clinical and Medical Case Reports, 2020)
We report a case of a 29-year-old pregnant patient: gravida3, para 3, abortus 0, 38 weeks . Her medical history included an idiopathic intracranial hypertension since 2014 with visual repercussions, without obstetric consequences treated with Acetazolamide 250 mg 1 tablet per day. Caesarean section was indicated for fetal distress. The context was urgent (fetal detress), and the anesthesiologist faced a dilemma of the choice of the anesthetic technique: spinal anesthesia or general anesthesia. Finally, a spinal anesthesia was performed by an expert without incidents. A healthy baby was delivered (Apgar score was 9/10). Idiopathic intracranial hypertension IIH is linked to a lack of absorption of cerebro-spinal fluid (CSF) in arachnoid granulations. Outside pregnancy the risk factors of IIH which have been evoked are polycystic ovary syndromes and blood coagulation anomalies as thrombophilia or. Even though the visual prognosis is compromised, there is no risk of engagement that would be life-threatening.